Teaching Romanian as a Foreign Language. Intercultural Approaches - Georgiana ARGĂSEALĂ (ACROSS, 2023)
The perspective of teaching Romanian as a foreign language is becoming increasingly evident, as demonstrated by the special attention it is starting to receive. The cultural and social space in which the teaching and learning of Romanian as a second language takes place is important as far as it influences the way in which a person acquires the skills to receive and produce a message, whether oral or written. But the act of teaching brings with it an innovative approach when the target group is not homogeneous in terms of age, nationality, religion, traditions, and customs. Thus, one of the challenges faced by teachers is the choice of the target language, especially when one or more members of the group have no or minimal knowledge of the target language.